From 3b9c576d6197393a224b47d9b7fedf875f3e0f1e Mon Sep 17 00:00:00 2001 From: Nikolai Kudasov Date: Wed, 13 Dec 2023 23:03:25 +0300 Subject: [PATCH] Save file that reproduces the formatting bug --- .../04-homotopies-and-equivalences.rzk.md | 60 +++++++++++++++++-- 1 file changed, 54 insertions(+), 6 deletions(-) diff --git a/src/1-foundations/2-homotopy-type-theory/04-homotopies-and-equivalences.rzk.md b/src/1-foundations/2-homotopy-type-theory/04-homotopies-and-equivalences.rzk.md index 450c036..a554754 100644 --- a/src/1-foundations/2-homotopy-type-theory/04-homotopies-and-equivalences.rzk.md +++ b/src/1-foundations/2-homotopy-type-theory/04-homotopies-and-equivalences.rzk.md @@ -403,14 +403,62 @@ which are discussed in Sections [2.6](06-cartesian-product-types.rzk.md) and [2. ### Transitivity -```rzk --- #def equivalence-trans --- (A B C : U) --- : equivalence A B → equivalence B C → equivalence A C --- := \ (f, isequiv-f) (g, isequiv-g) → +``` +#define qinv-trans + ( A B C : U) + ( f : A → B) + ( g : B → C) + : qinv A B f → qinv B C g → qinv A C (compose A B C g f) + := + \ (f⁻¹ , (α-f , β-f)) (g⁻¹ , (α-g , β-g)) → + ( compose C B A f⁻¹ g⁻¹ + , ( \ c → + path-concat C + ( g (f (f⁻¹ (g⁻¹ c)))) + ( g (g⁻¹ c)) + ( c) + ( ap B C g + ( f (f⁻¹ (g⁻¹ c))) + ( g⁻¹ c) + ( α-f (g⁻¹ c))) + ( α-g c) + , \ a → + path-concat A + ( f⁻¹ (g⁻¹ (g (f a)))) + ( f⁻¹ (f a)) + (a) + ( ap B A f⁻¹ + (g⁻¹ (g (f a))) + (f a) + ( α-f (g⁻¹ c))) + ( α-g c))) + +#def equivalence-trans + ( A B C : U) + : equivalence A B → equivalence B C → equivalence A C + := + \ (f , isequiv-f) (g , isequiv-g) → + ( \ ((f⁻¹ , (α-f , β-f)) : (qinv A B f)) ((g⁻¹ , (α-g , β-g)) : (qinv B C g)) → + ( compose A B C g f + , qinv-to-isequiv A C (compose A B C g f) + ( compose C B A f⁻¹ g⁻¹ + , ( \ c → path-concat C -- g f f⁻¹ g⁻¹ c = g g⁻¹ c = c + ( g (f (f⁻¹ (g⁻¹ (c))))) + ( g (g⁻¹ (c))) + ( c) + ( ap B C g (f (f⁻¹ (g⁻¹ (c)))) (g⁻¹ (c)) (α-f (g⁻¹ (c)))) + ( α-g c) + , \ a → path-concat A -- f⁻¹ g⁻¹ g f a = f⁻¹ f a = a + ( f⁻¹ (g⁻¹ (g (f (a))))) + ( f⁻¹ (f (a))) + ( a) + ( ap B A f⁻¹ (g⁻¹ (g (f (a)))) (f (a)) (β-g (f (a)))) + ( β-f a))))) + ( isequiv-to-qinv A B f isequiv-f) + ( isequiv-to-qinv B C g isequiv-g) ``` - +## Proof of Corollary 2.4.4 ``` title="Proof for corollary 2.4.4. Homotopy with id" lemma 2.4.3 : H(x) • g (p) = f (p) • H y